PROPUESTA DEL PLAN DE MARKETING TURISTICO DE LOS ATRACTIVOS NATURALES Y CULTURALES DE LA PARROQUIA RURAL NAMBACOLA DEL CANTÓN GONZANAMÁ PROVINCIA DE LOJA - Herrera Samaniego, Thalia Cecibel (2016)
There is a unique biodiversity in the Ecuador, each province has different other features. Tourism is has been transformed into development processes primarily when tourist demand is notable within a small stage where the results are positive especially when the growth of tourist infrastructure highlights the importance of investing in the hotel and gastronomic, appearance due to a gradual demand from years ago and with the passage of time has grown by promoting national and global. In the province of Loja, Gonzanamá canton and in particular the parish Nambacola stands out for its beautiful landscapes, variety of flora fauna, handicrafts and beautiful the same attractions that have not been promoted due to the lack of dissemination thereof; taking into account these considerations, it has developed this research work, the so-called theme is: "PLAN of MARKETING to the attractive natural and cultural of LA parish NAMBACOLA of the CANTON GONZANAMÁ province of LOJA", with the approach of General and specific objectives. He was raised as a general objective the development of a marketing plan for the natural and cultural attractions of the Nambacola parish of the Canton Gonzanamá, enclosing a proposal from advertising and promotion with the use of the media, advertising, information points and tourist guides. As specific objectives has set goals and strategies that go hand in hand with the General that allowed to find a solution to this social problem as a diagnosis of the natural and cultural attractions of the parish Nambacola of canton Gonzanamá province of Loja; Propose a plan of Marketing tourist for the natural attractions and cultural Nambacola parish and socialize the plan of tourist marketing of the natural and cultural attractions of the parish Nambacola of the Canton Gonzanamá in the province of Loja with authorities and the community in general.Within the Marketing Plan was necessary the use of methodology that facilitated the fulfilment of objectives paths, to the first specific objective, we used the following methods; Deductive: that comprised a general analysis of the environment of this parish location, population factor demographic, economic, socio-cultural, political, and technological factor; inductive: which allowed to internalize us in the problems of this population to determine the lack of tourism promotion that allows itself an economic growth of its inhabitants; Ddescriptivo: detailed exposure of sites attractive and paradise; History: which is based on the knowledge of their ancestors and to shape its legends through the promotion of tourism. Not leaving aside the importance of the use of techniques like the survey that was applied to the inhabitants of the place, the interview that was applied to the President of the vestry who contributed positively to the location of the shortcomings by the absence of a tourism promotion of this parish as general information; and the observation, that without them, the achievement and fulfilment of the aforementioned objectives had not been able to meet. A key part was the development of the matrix SWOT, where they investigated the strengths, opportunities, weaknesses and threats, through assessment of the internal and external factors you could meet what are affecting the tourist promotion of the parish. The development of second specific objective, which is the proposal of the Marketing Plan that contains the implementation of a plan of advertising and strategic promotion, such as the creation of a tourist information point; ending with a plan for training and the promotion of a tourist package, which was carried out through the descriptive and inductive method that allowed explain as clear market strategies.The third specific objective, the socialization of the Marketing Plan with authorities of the vestry and stakeholders was the technique of Marp, through three phases (previous, execution and results.It can be concluded that the parish Nambacola has very important tourist attractions that would come to constitute a contribution to economic development; with a proper promotion would be achieved by attracting tourists who thus encourages residents to invest and achieve the growth of the parish, creating sources of work and the improvement of their quality of life; attention to the customer, tourist services, guidance training make that Nambacola is not improved economically.It is recommended to GAD timely care in the maintenance of the trails, the location of appropriate signage to tourist attractions; achieve the intervention of the authorities of the parish to turn bodies specialised in tourism to undertake activities that promote this parish,thus giving the possibility of having a plant or tourist office within it.